2022
DOI: 10.26858/cjpko.v14i1.32521
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Scientific Approach Using Problem Based Learning (PBL) Models to Improve Learning Outcomes of Overhand Pass In Volleyball Game

Abstract: This study is a classroom action research that aims to discover whether a scientific approach using a problem-based learning model can improve the learning outcomes of upper passing in volleyball for grade XI MIPA 2 at Ma Ma’arif Nu Lasepang in the Bantaeng district. A classroom action research employed the PBL model in its material, namely the basic technique of upper passing in a volleyball. The study was conducted in 2 cycles, each cycle consisted of 3 meetings. The aspects assessed in this study were spiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Aslam, L. K et al [19] concluded that PBL could obviously facilitate improvement of skills of learners. Utami, I et al [20] applied PBL to teaching basic skills of volleyball passing, finding that in the first cycle, PBL increased the number of students skilled in passing. Winning, T et al [21] found that PBL can provide an incentive learning environment, promote comprehensive learning, encourage systematic patient management methods, and develop independent learning skills.…”
Section: 2mentioning
confidence: 99%
“…Aslam, L. K et al [19] concluded that PBL could obviously facilitate improvement of skills of learners. Utami, I et al [20] applied PBL to teaching basic skills of volleyball passing, finding that in the first cycle, PBL increased the number of students skilled in passing. Winning, T et al [21] found that PBL can provide an incentive learning environment, promote comprehensive learning, encourage systematic patient management methods, and develop independent learning skills.…”
Section: 2mentioning
confidence: 99%
“…Mereka berpendapat bahwa tugasnya hanyalah menyampaikan sejumlah materi pengetahuan kepada sejumlah siswa tertentu di dalam kelas tertentu pula (Rohmansyah, 2017). Guru-guru tersebut hanya berusaha menguasai materi bahan pelajaran yang akan disampaikannya dan sedikit pengetahuan tentang cara menyampaiakannya (Utami et al, 2022). Guru seperti itu tidak akan lebih JPKMBD (Jurnal Pengabdian Kepada Masyarakat Bina Darma) Vol.…”
Section: Pendahuluanunclassified
“…Learning is assistance provided by educators so that the process of acquiring knowledge and knowledge can occur, mastering skills and character, as well as forming attitudes and beliefs in students (Saitya, 2022). Changes as a result of the learning process can be proposed in various forms such as changes in knowledge, understanding, attitudes and behaviour, skills, abilities and abilities, reaction power, receptiveness and other aspects that exist in individuals who learn (Utami et al, 2022).…”
Section: Introductionmentioning
confidence: 99%